mSphere of influence: modifying an old method to study RNA-protein interactions - Tiengwe,C (mSphere, 2019)
Calvin Tiengwe works on posttranscriptional gene regulation and iron homeostasis in the parasitic protozoan Trypanosoma brucei. In this mSphere of Influence article, he reflects on how the paper “Comprehensive identification of RNA-protein interactions in any organism using orthogonal organic phase separation (OOPS)” by Queiroz et al. (Nat Biotechnol 37:169–178, 2019, https://doi.org/10.1038/s41587-018-0001-2) influenced his research by providing a tool to capture RNA-protein complexes on a global scale using acid guanidinium thiocyanate-phenol-chloroform (AGPC), an old method hitherto applied for RNA, DNA, or protein purification.